Effects of Intrinsic Pentagon Defects on Electrochemical Reactivity of Carbon Nanomaterials. (14th February 2019) - Zhu, Jiawei; Huang, Yupeng; Mei, Wencen; Zhao, Chenyang; Zhang, Chengtian; Zhang, Jian; Amiinu, Ibrahim Saana; Mu, Shichun
Abstract: Theoretical calculations reveal that intrinsic pentagons in the basal plane can contribute to the local electronic redistribution and the contraction of band gap, making the carbon matrix possess superior binding affinity and electrochemical reactivity. To experimentally verify this, a pentagon‐defect‐rich carbon nanomaterial was constructed by means of in situ etching of fullerene molecules (C60 ). The electrochemical tests show that, relative to hexagons, such a carbon‐based material with abundant intrinsic pentagon defects makes much greater contribution to the electrocatalytic oxygen reduction activity and electric double layer capacitance. It shows a four‐electron‐reaction mechanism similar to commercial Pt/C and other transition‐metal‐based catalysts, and a higher specific capacitance than many reported metal‐free carbon materials. These results show the influence of intrinsic pentagon defects for developing carbon‐based nanomaterials toward energy conversion and storage devices. Abstract : Intrinsische Pentagondefekte in Kohlenstoffmaterialien tragen in hohem Maß zur elektrokatalytischen Sauerstoffreduktionsaktivität und elektrischen Doppelschichtkapazität bei. Wenn Pentagondefekte mit Stickstoff‐Dotierungen kombiniert werden, zeigt das erhaltene Material vielversprechende Eigenschaften für die Anwendung in Zn‐Luft‐Batterien (im Bild links) und Superkondensatoren (rechts).